A search for near infrared counterparts of three pulsar wind nebulae - Curran, Peter; Chaty, S.; Zurita Heras, J.; Coleiro, A. (EDP Sciences, 2011)
Context. While pulsar wind nebulae (PWNe) and their associated isolated pulsars are commonly detected at X-ray energies, they aremuch rarer at near infrared (nIR) and optical wavelengths.Aims. Here we examine three PWN systems in the Galactic plane – IGR J14003-6326, HESS J1632-478 and IGRJ18490-0000 – ina bid to identify optical/nIR emission associated with either the extended PWNe or their previously detected X-ray point sources.Methods. We obtain optical/nIR images of the three fields with the ESO – New Technology Telescope and apply standard photometricand astrometric calibrations.Results. We find no evidence of any extended emission associated with the PWNe in any of the fields; neither do we find anynew counterparts to the X-ray point sources, except to confirm the magnitude of the previously identified counterpart candidate ofIGRJ18490-0000.Conclusions. Further observations are required to confirm the association of the nIR source to IGR J18490-0000 and to detectcounterparts to IGRJ14003-6326 and HESS J1632-478, while a more accurate X-ray position is required to reduce the probabilityof a chance superposition in the field of the latter.